An overview of adult health outcomes after preterm birth. (November 2020) - Crump, Casey
Abstract: Preterm birth (gestational age < 37 completed weeks) has increased in prevalence in most countries in the past 20 years and now affects nearly 11% of all births worldwide. Because of treatment advances introduced in the 1970s–1980s, >95% of preterm infants who receive modern neonatal and pediatric care now survive into adulthood. The earliest birth cohorts to benefit from those advances are now in their 4th and 5th decades of life. A growing number of large cohort studies have investigated the long-term health sequelae in adulthood. Evidence has consistently shown that adult survivors of preterm birth have increased risks of chronic disorders involving various organ systems, including cardiovascular, endocrine/metabolic, respiratory, renal, neurodevelopmental, and psychiatric disorders, which either persist from childhood into adulthood or sometimes first manifest in adulthood. These disorders also lead to moderately (30% to 50%) increased mortality risks during early to mid-adulthood among persons born preterm compared with full-term, and even higher risks among those born at the earliest gestational ages. However, the majority of persons born preterm have low absolute risks of these outcomes and good self-reported quality of life in adulthood. Priorities for future research include the assessment of long-term health sequelae of preterm birth in racially and economically diverse populations, additional follow-up of existing cohorts into older adulthood, elucidation of outcomes by preterm birth subtype (e.g., different underlying causes) to improve risk stratification, and identification of protective factors that will support the long-term health trajectory and well-being of preterm-born adults.